The Influence of Work Environment, Job Skills, and Work Engagement on Employee Productivity in MSMEs - Naurah Rama Faadhilah; Dewi Andriani; Vera Firdaus (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Employee productivity is a critical factor in the success of Micro, Small, and Medium Enterprises (MSMEs). This study explores the influence of the work environment, job skills, and work engagement on employee productivity. MSMEs are instrumental in economic development, yet they face challenges such as fluctuating market demand, competition, and workforce management. A positive work environment and high employee engagement are essential for sustaining productivity, while job skills play a foundational role in task performance. The research employed a quantitative approach, gathering data from 107 employees through questionnaires, field observations, and secondary sources. Data analysis was conducted using the Partial Least Squares (PLS) method to evaluate the relationships between variables. The findings reveal that the work environment and work engagement have significant positive effects on employee productivity, whereas job skills show no statistically significant impact. This suggests that while technical and non-technical abilities are important, they are insufficient without supportive environmental and psychological factors. The study highlights the need for MSMEs to prioritize creating a conducive work environment that fosters collaboration, comfort, and safety. Employee engagement should also be enhanced through participatory decision-making and recognition programs to instill a sense of ownership and commitment. Furthermore, regular training programs should align job skills with operational requirements, ensuring employees are well-equipped to meet organizational goals.